Melatonin attenuates smoking‐induced hyperglycemia via preserving insulin secretion and hepatic glycogen synthesis in rats. Issue 4 (25th March 2018) - Li, Tianjia; Ni, Leng; Zhao, Zhewei; Liu, Xinnong; Lai, Zhichao; Di, Xiao; Xie, Zhibo; Song, Xitao; Wang, Xuebin; Zhang, Rui; Liu, Changwei
Abstract: Epidemiology survey indicated that cigarette smoking is a risk factor of diabetes. However, the precise mechanisms remain to be clarified. In this study, we found that smoking caused metabolic malfunctions on pancreas and liver in experimental animal model. These were indicated by hyperglycemia, increased serum hemoglobin A1c level and decreased insulin secretion, inhibition of liver glycogen synthase (LGS), and hepatic glycogen synthesis. Mechanistic studies revealed that all these alterations were caused by the inflammatory reaction and reactive oxygen species (ROS) induced by the smoking. Melatonin treatment significantly preserved the functions of both pancreas and liver by reducing β cell apoptosis, CD68‐cell infiltration, ROS production, and caspase‐3 expression. The siRNA‐knockdown model identified that the protective effects of melatonin were mediated by melatonin receptor‐2 (MT2). This study uncovered potentially underlying mechanisms related to the association between smoking and diabetes. In addition, it is, for first time, to report that melatonin effectively protects against smoking‐induced glucose metabolic alterations and the signal transduction pathway of melatonin is mainly mediated by its MT2 receptor. These observations provide solid evidence for the clinically use of melatonin to reduce smoking‐related diabetes, and the therapeutic regimens are absent currently.